Adaptasi nelayan terhadap perubahan cuaca. - Hayrol Azril Mohamed Shaffril (Serdang: Universiti Putra Malaysia, 2013)
On fisheries and environmental aspects of climate changes in Malaysia
Keywords: Fisheries -- Malaysia; Fishes -- Climatic factors -- Malaysia; Fishes -- Environmental aspects -- Malaysia